Optimalisasi Pembelajaran Seni Musik: Studi Komparatif Strategi Drill and Practice dan Kooperatif Learning - Sekar Niwana; Hafid Zuhdan Bahtiar (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: The objective of this study was to compare the effectiveness of two learning strategies, cooperative learning and drill and practice, in enhancing musical skills among students at SMP N 1 Kertek. A comparative study was conducted at SMP N 1 Kertek, where students participated in both strategies. Cooperative learning involved dividing students into small groups to collaboratively solve rhythmic problems, while drill and practice focused on independent practice using a recorder. Method: The research employed a qualitative approach with a case study design. Data was gathered through classroom observations, interviews with teachers and students, and analysis of evaluation documentation. Results and Discussion:The results indicated that both strategies significantly contributed to improving students' musical skills. Cooperative learning facilitated collaboration among students and enhanced conceptual understanding, while drill and practice effectively improved practical skills in playing musical instruments. The use of audio-visual media was also found to strengthen students' understanding of the learning material. Conclusion: the combination of cooperative learning and drill and practice, supported by audio-visual media, provided a comprehensive and engaging approach to music education at SMP N 1 Kertek. This approach not only enhanced students' musical skills but also fostered a dynamic and enjoyable learning environment. The implications of this study can serve as a guideline for developing more effective music education methods in other schools.